1996
DOI: 10.1128/jb.178.4.1047-1052.1996
|View full text |Cite
|
Sign up to set email alerts
|

Galactofuranose biosynthesis in Escherichia coli K-12: identification and cloning of UDP-galactopyranose mutase

Abstract: We have cloned two open reading frames (orf6 and orf8) from the Escherichia coli K-12 rfb region. The genes were expressed in E. coli under control of the T7lac promoter, producing large quantities of recombinant protein, most of which accumulated in insoluble inclusion bodies. Sufficient soluble protein was obtained, however, for use in a radiometric assay designed to detect UDP-galactopyranose mutase activity (the conversion of UDP-galactopyranose to UDP-galactofuranose). The assay is based upon high-pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
170
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(175 citation statements)
references
References 25 publications
4
170
0
1
Order By: Relevance
“…6C), while no reaction was observed in assays lacking a cofactor or in assays with NAD or NADP (data not shown). Other than the cofactor requirements, these data are in agreement with the data de- scribed for Glf of E. coli (48) and further support the conclusion that p37 indeed is UDP-Galf.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…6C), while no reaction was observed in assays lacking a cofactor or in assays with NAD or NADP (data not shown). Other than the cofactor requirements, these data are in agreement with the data de- scribed for Glf of E. coli (48) and further support the conclusion that p37 indeed is UDP-Galf.…”
Section: Resultssupporting
confidence: 81%
“…Based on chemical analysis of the reaction products obtained by acid and alkaline hydrolosis as well as periodate oxidation, Trejo et al (46) predicted that the sugar nucleotide is UDP-Galf. More recently, Nassau et al (48) cloned the glf gene of E. coli and showed that it encodes UDP-galactopyranose mutase (EC 5.4.99.9). Nassau et al (48) concluded that the reaction product of the UDP-galactopyranose mutase reaction is UDP-Galf based on HPLC analysis of the sugar 1-phosphate obtained after phosphodiesterase treatment of the reaction product.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…or (4) alternatively, would the latter be incorporated into a macromolecule via a UDP-Gal f precursor? Nassau et al (1996), have been able to obtain clones of UDP-galactopyranose mutase from E. coli K-12 capable to convert reversibly UDP-gal p to UDP-gal f with the equilibrium favoring the formation of the pyranoic compound. More recently, mutases have been cloned in Klebsiella pneumoniae (Koplin et al 1997) and Mycobacteria (Weston et al 1998).…”
Section: Lppg and Galactofuranosementioning
confidence: 99%